La técnica Yin: Teoría y práctica del discurso persuasivo en China durante los Reinos Combatientes (SS. V-III A.C.) - Juan Luis Conde Calvo; David Sevillano López; Ziqiao Meng (Talia dixit, 2020)
The authors of this paper translate from Classical Chinese and comment on various texts that are intended to illustrate the relationship between the theory and practice of persuasive discourse during the Warring States period (5th to 3rd centuries BC). The texts come from two different works: Zhanguoce, a compilation of pre-Qin documents made by Liu Xiang in the Han period (late 1st century BC), and Lüshi Chunqiu, an encyclopedic collection undertaken under the instructions of Lü Buwei, Qin State Minister, in the 3rd century BC. The political suasoria (shuì) has the counselor and the king as protagonists par excellence. In the anecdotes that provide concrete examples of the rhetorical exercitatio, an approach decidedly marked by the unequal power relations between both of them is observed, where dialogue dominates on monologue. Under such conditions, the persuader develops an indirect strategy that, disdaining any virtuosity of elocution, tries first and foremost not to challenge the expectations of his one-person audience.